(untitled) (Scientific Journal of Actuarial Finance and Accounting, 2025)
The current trends of rapid development in the global tourism and hospitality industry determine the necessity of shifting towards more practical and competency-based education models. This research examines the feasibility of integrating the dual education systems into the national curricula on tourism and hospitality. The study discovers the existing gap between the academic learning outcomes and the industry requirements, which is relevant to developed countries, such as Uzbekistan, where the local government views tourism as a priority economic industry. The research is based on the qualitative-descriptive method, which implies the analysis of curricula, interviews with educators and industry specialists as well as the comparative examination of dual education models implemented in the tourism industry of European countries. The research outcomes indicated that dual education improves the employability of the graduates and enhances their professional skills and competencies making them more appropriate for the industry. At the same time, due to structural constraints, the lack of university-insustry partnership and sufficient regulation results in the failure of the system’s implementation, implying a number of barriers to the sustainable integration. The research proves that for effective tourism education transformation, the system requires the university, government, and industry support of dual education policy beneficial initiatives, the industry-oriented transformation in curriculum and close collaboration networks. The theoretical implications suggest for understanding the complexity of the field through the analysis of conceptual frameworks regarding human capital and application of the theoretical insights to the development of the superstructure of renewed tourism education system.